A new fiscal framework for Ireland - Lane, Philip R. (Statistical and Social Inquiry Society of Ireland, 2010)
Pro-cyclicality in Irish fiscal policy has contributed to macroeconomic volatility over recent decades. Accordingly, this paper seeks to identify institutional mechanisms that can improve the performance of fiscal policy in macroeconomic stabilisation in Ireland. We propose a new fiscal framework for Ireland that combines the adoption of a rules-based approach to budgetary policy with the appointment of an independent fiscal policy council that will be formally involved in the fiscal process. Finally, we also advocate a set of ancillary reforms that will further improve the coherence of Irish fiscal policy with membership of European Monetary Union.
(read before the Society, 11 February 2010)
Keywords: Fiscal policy; Macroeconomic stabilisation; Cylicality; 314.15